2017
DOI: 10.1590/0103-6440201701059
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of a New Dental Glass Ionomer Cement with Cellulose Microfibers and Cellulose Nanocrystals

Abstract: Developing new restorative materials should avoid damage to tissue structures. This study evaluated the biocompatibility of a commercial dental glass ionomer cement (GIC) mechanically reinforced with cellulose microfibers (GIC+CM) or cellulose nanocrystals (GIC+CN) by implantation of three test specimens in subcutaneous tissue in the dorsal region of 15 Rattus norvegicus albinus rats. Each rat received one specimen of each cement, resulting in the following groups (n=15): Group GIC (Control), Group GIC+CM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The latter are discussed in more detail in the following section and, for the moment, results for the cellulose fibres only will be considered. In fact, these fibres were found to have only slight effects on the mechanical properties of the glass-ionomers (compressive strength, Young's modulus, and diametral tensile strength) though, by contrast, biocompatibility was enhanced [79]. Fibres were added to the commercial conventional glass-ionomer Vidrion R (S.S. White, Brazil), a material with a reported compressive strength of only 49.15 MPa [78], which is too low for clinical use according to the relevant ISO standard [32].…”
Section: Fibre Reinforcementmentioning
confidence: 96%
See 1 more Smart Citation
“…The latter are discussed in more detail in the following section and, for the moment, results for the cellulose fibres only will be considered. In fact, these fibres were found to have only slight effects on the mechanical properties of the glass-ionomers (compressive strength, Young's modulus, and diametral tensile strength) though, by contrast, biocompatibility was enhanced [79]. Fibres were added to the commercial conventional glass-ionomer Vidrion R (S.S. White, Brazil), a material with a reported compressive strength of only 49.15 MPa [78], which is too low for clinical use according to the relevant ISO standard [32].…”
Section: Fibre Reinforcementmentioning
confidence: 96%
“…This was despite the fact that there appeared to be no chemical reaction between the cellulose nanocrystals and the cement matrix, as shown by the absence of any changes in the FTIR spectra [89]. Like the addition of cellulose microfibres, the nanocrystals enhanced the biocompatibility of the cements [79] and, overall, showed promise as additives for these cements.…”
Section: Nanoparticle Reinforcementmentioning
confidence: 99%
“…Glass ionomer cement is regarded as an imperative revolutionary in restorative dentistry, due to its chemical adhesion to tooth, coefficient of thermal expansion close to tooth structures, biocompatibility, and fluoride release. Yet, this cement present some drawbacks with regards to mechanical integrity and load bearing capacity ( 18 ). Previous literature has verified significantly greater mechanical and bond strength for RMGICs compared to the conventional GIC.…”
Section: Discussionmentioning
confidence: 99%
“…According to Silva et al ., the addition of CNC fibers with a concentration above 1% lead to the composites mechanical failure due to the aggregation of nanoparticles. It has been reported that owing to the specificity of the nanomaterials, extremely low concentrations are needed for material augmentation ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glass ionomer cement has a wide application area because of its advantages. However, its use on permanent teeth at locations facing occlusal forces is restricted, and that is why several strategies are followed to enhance the mechanical properties, such as incorporation of powdered silver-tin amalgam alloy, cermet, stainless still, gold, oxides of titanium, palladium, niobium, strontium or zirconium, ytterbium fluoride, barium or magnesium sulphate, whiskers/fibres/crystals of aluminium silicate, silicon carbide, zirconia, aluminium, carbon, or cellulose, reactive glass/bioglass, fluorinated graphene, hydroxyapatite, fluorapatite, N-vinyl pyrrolidone, bioactive apatite with zirconia or nanosilica complex, nanochitosan, organic derivative of montmorillonite or even chicken eggshell powder [105][106][107][108][109][110][111][112][113][114].…”
Section: Nature-inspired Materials -A Step Ahead In Dental Materialsmentioning
confidence: 99%